EFEKTIVITAS METODE DISKUSI DALAM MENINGKATKAN PRESTASI BELAJAR SISWA DALAM MATA PELAJARAN AKIDAH AKHLAK DI MI AINUL ULUM 01 KAROBELAH MOJOAGUNG JOMBANG - Shofwatal Qolbiyyah; Eko Hadi Wardoyo (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2024)
This research aims to describe the effectiveness of the discussion method in improving student learning achievement in the Aqidah Akhlak subject and determine the influencing factors at MI Ainul Ulum 01 Kerobelah Mojoagung Jombang. This research uses a qualitative descriptive approach, so the presence of researchers in the field is very important. Data in the form of words was obtained from informants, while additional data was in the form of documents. The data collection technique is through interviews, observation and documentation. Meanwhile, data analysis is carried out by reviewing existing data, presenting data, and drawing conclusions/verifying data. The results of this research show that the effectiveness of the discussion method has a positive impact in improving student learning achievement in the Aqidah Akhlak subject. Evidence that this learning process is effective is that students are interested, motivated, interested and active during the learning process using the discussion method.